Effective Utilization of Laboratory Information System to Triage Troponin Critical Value Notification to the Emergency Department. (11th September 2019) - Pomper, Gregory; Hunt, Matt; Van Dyke, Erica; Waldron, Johanna; Hiestand, Brian; Wong, Steven
Abstract: Objectives: The laboratory received a request to report abnormal troponin (ab-TnI) as critical values (CVs) for ED patients. The laboratory information system (LIS) was programmed to identify only ED patients presenting with an ab-TnI. Only the first ab-TnI on presentation was critical. Unnecessary laboratory CV communications could impair overall turnaround time. Methods: Mean troponin, ab-TnI test volumes, and ab-TnI from ED patients with suspected acute coronary syndrome were determined. The LIS team constructed a best practice alert in the Beaker module (EPIC, Verona, WI). The ab-TnI CV build filtered patients based on ab-TnI values and ED location. Based on pilot data, the build was adjusted to limit ab-TnI alerts to only the first ab-TnI result. The amended build logic was to trigger the alert if an ED location TnI was abnormal. At trigger, if the lowest TnI result in the last 24 hours is ≤0.040, the return "true." If true, then no TnI >0.040 in the last 24 hours, call the ED because they currently have a result >0.040. If the answer is "false, " then do not call the ED. If the patient had no TnI in the last 24 hours, then the alert would be triggered as well. The system was piloted after education to the ED and laboratory teams. Results: The mean TnI per day was 150; the mean ab-TnI was 63 (42%), of which 1.1 ab-TnI originated from the ED. After pilot go-live, the actual number of ab-TnI/day was 14.3. The alert logic was amended to limit the trigger to the first ab-TnI result, reducing the CV volume to 9.6/day. Conclusion: The LIS can be leveraged to develop a clinically valuable and operationally manageable critical value alert system. Clinical and laboratory teams must be open to amending the process as needed to achieve success.